Application of Honey and Transparent Dressing to Split Thickness Skin Graft Donor Site and Its Effect on Epithelialization Rate - A., Teuku; P., Nandita Melati; Sudjatmiko, Gentur; S., Asrofi; D., Ishandono (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: Split thickness skin graft (STSG) is one of the modalities used to close a defect. The donor site can be healed secondarily with tulle grass and moist gauze after 14 days and with transparent dressing will take about 10-13 days. Recently the wound healing by using honey application has been used. Whether or not using honey application with transparent dressing will hasten the epithelialization rate of the STSG donor site is now in question. Method: This research is an open, non-randomized clinical trial with a parallel design and intervention using honey application with transparent dressing. A total of 19 patients (7 female and 8 male) were included in this study. The reapplication of honey was done every two days. The patients was followed up every day, with clinical photograph taken and complaints such as pain, odor and infection noted. Results: The mean epithelialization rate of the donor site treated with honey and transparent dressing was 9,74 (+0,24) days compared to 10,79 (+1,23) days in the transparent-dressing-only group (p=0,00). Conclusion: The application of honey with transparent dressing to cover for STSG donor site led to a faster epithelialization rate, less odor and less pain. Commercial honey was used, and readily available.